Dynamic of Psyhological Well-Being Early Adults Growing Up in a Broken Home Family - Salsabila, Amirafatin; Darmawanti, Ira (Character Jurnal Penelitian Psikologi, 2023)
This study focuses on the dynamics of psychological well-being of early adults growing up in a broken home family with the following subject criteria: female aged 21-40 years, coming from a broken home family whose parents are divorced, now living with step family. Data collection was carried out through semi-structured interviews with three relevant respondents and closest people. The results of the study were analyzed using thematic qualitative methods. The results reveal two major themes, such as the background to the divorce and the dynamics of psychological well-being. Then several sub-themes emerged, namely events at the time of divorce, the impact of divorce, bad experiences, feelings that emerged, thoughts that emerged, and the six aspects of psychological well-being. Respondents in this study showed feelings of sadness, disappointment, anger which had various impacts including decreased achievement and even self-harm behavior. From the dynamics of this incomplete family background, two out of three research respondents showed more positive results compared to one other respondent who showed stagnant results in the psychological well-being of each individual.